METODE ELIPSOIDA KESALAHAN SEBAGAI METODE ALTERNATIF UNTUK ANALISIS LOKASI RAWAN KECELAKAAN LALU LINTAS - Priyantha Wedagama, D.M (Jurnal Ilmiah Teknik Sipil; Vol. 14, No. 1 Januari 2010)
Ellips Errors were constructed to analyse pedestrian accidents concentrations in Newcastle, England. More specifically, Ellips Errors were used to analyse both spatial and temporal patterns of pedestrian accidents. Having observed these patterns, cyclic pedestrian accidents would be able to be identified. The study results showed that high accident concentration occurred in the Newcastle city centre area. These were indicated with both centroids and distributions (shown as ellips area) of pedestrian accidents. Top priority on pedestrian accidents reduction, therefore, should be paid more on the city centre area. The best result for using this Ellips Error method in Indonesia will be achieved through integrated road accidents recording system by means of Global Positioning System (GPS) and Geographic Information System (GIS). Geographic position of road accidents and detailed maps of the urban area, i.e. 1:1000 on scale, are required for this Ellips Error method.
Keywords: Ellipse Error, Spatial Data, Pedestrian Accidents.